STUDENTS’ PERCEPTIONS REGARDING THE TABLET PERSONAL COMPUTER (PC) AS A MOBILE LEARNING DEVICE AT A GRADUATE INSTITUTE IN TSHWANE: AN EXPLORATORY STUDY - Cant, MC; Perpetual Enock, JA Wiid (Universitas Nurul Jadid, 2021)
The unfolding Fourth Industrial Revolution (FIR) has necessitated immense technological innovations in the educational sphere. To date, countable educational institutions in South Africa have introduced the Tablet Personal Computer (PC) to their students for academic purposes. However, perceptions regarding the Tablet PC as a mobile learning device has not been delved into in South Africa. This study has done such an exploration. The study explores the perceptions that graduate students in Tshwane hold of the Tablet Personal Computer (PC) as a mobile learning and management device. Data was collected from full-time undergraduate students using a web based online survey with a semi-structured questionnaire. A population sample of 277 respondents was selected using non-probability method in the form of convenience sampling. Data was analysed using descriptive and inferential statistics methods. The results of the study indicated that the majority of the surveyed students had a positive perception regarding the Tablet PC. Based on the research findings, limitations, recommendations and future research opportunities were suggested.